The Role of Anesthesia Practitioners in Implementing Sterilization and Infection Prevention Standards in Collaboration with Sterilization Personnel in Operating Rooms (The Review of Diabetic Studies, 2024)
Anesthesia practitioners play a central role in infection prevention within the operating room by enforcing aseptic techniques and ensuring proper sterilization of semi-critical devices such as laryngoscopes and intravenous connectors. This work examines the evolution and integration of sterilization standards into anesthesia care, highlighting the importance of interdisciplinary collaboration between anesthesia teams and sterilization personnel. Key factors influencing contamination prevention include hand hygiene compliance, environmental cleaning of anesthesia workspaces, and adherence to validated disinfection protocols. Critical control points are identified where microbial transmission risk is highest, including airway device preparation, vascular access handling, and ultrasound-guided procedures. Challenges in high-volume surgical centers are addressed by proposing system designs that balance operational efficiency with uncompromising safety standards, incorporating workflow adaptations, resource allocation, and real-time monitoring. Ethical considerations emphasize patient rights through informed consent processes that communicate infection risks and preventive measures transparently. Embedding aseptic practices into anesthesia workflows requires coordinated behavioral, technical, and organizational strategies to reduce healthcare-associated infections and enhance patient safety during perioperative care.